2023
DOI: 10.3389/fmolb.2023.1096326
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the epithelial-to-mesenchymal plasticity in a small cell lung carcinoma (SCLC) and lung fibroblasts co-culture model

Abstract: The tumor microenvironment (TME) is the source of important cues that govern epithelial-to-mesenchymal transition (EMT) and facilitate the acquisition of aggressive traits by cancer cells. It is now recognized that EMT is not a binary program, and cancer cells rarely switch to a fully mesenchymal phenotype. Rather, cancer cells exist in multiple hybrid epithelial/mesenchymal (E/M) states responsible for cell population heterogeneity, which is advantageous for the ever-changing environment during tumor developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 93 publications
2
14
0
Order By: Relevance
“…Reciprocally, the process of EMT induces cellular changes that result in ECM remodeling creating a feedback loop that is tightly regulated in healthy tissues but is deregulated in cancer 43 . This cell interaction has recently been demonstrated in SCLC using a lung fibroblast coculture model 8 . Therefore, the consequences of ECM remodeling extend to the SCLC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reciprocally, the process of EMT induces cellular changes that result in ECM remodeling creating a feedback loop that is tightly regulated in healthy tissues but is deregulated in cancer 43 . This cell interaction has recently been demonstrated in SCLC using a lung fibroblast coculture model 8 . Therefore, the consequences of ECM remodeling extend to the SCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…3 While the mechanisms of chemoresistance have not yet been fully elucidated, recent research has shown that processes such as epithelial to mesenchymal transition (EMT) are now known to play a role 4,5 and fibroblasts, and extracellular matrix (ECM) proteins such as collagens, laminins, fibronectin, and proteoglycans, 6 promote this transition. 7,8 Moreover, patients with SCLC often present with symptoms of advanced disease, including weight loss, fatigue, and poor wound healing, 1 with an increased risk of thromboembolism. 9 Although the mechanisms are not fully understood, the abnormal production of procoagulant factors, such as tissue factor, von Willebrand factor, or fibrinogen, may be involved, 9 and thromboembolism continues to be a significant cause of cancer-related mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, epithelial cells can activate various EMT programs to varying degrees, and usually acquire many but not all of the characteristics related to complete mesenchymal cells. 15 This plasticity of cell phenotype may play an important role in the last step of the transfer cascade, namely the colonization of micro-metastatic deposits to form macroscopic tumors, as indicated by mouse and patient-derived xenograft (PDX) models. 16 Over the past two decades, the importance of the EMT program in tumor progression has been established, and an increasing number of studies have shown that the EMT program is activated during malignant progression.…”
Section: Role Of Emt In Escc Initiation and Progressionmentioning
confidence: 99%
“…It is worth noting that under all these pathological conditions, epithelial cells rarely activate the EMT program and EMT is typically reversible in normal epithelial cells and their tumor derivatives. Additionally, epithelial cells can activate various EMT programs to varying degrees, and usually acquire many but not all of the characteristics related to complete mesenchymal cells 15 . This plasticity of cell phenotype may play an important role in the last step of the transfer cascade, namely the colonization of micro‐metastatic deposits to form macroscopic tumors, as indicated by mouse and patient‐derived xenograft (PDX) models 16 …”
Section: The Mechanism Of Escc Occurrence and Its Influencing Factorsmentioning
confidence: 99%